2020
DOI: 10.1155/2020/7020924
|View full text |Cite
|
Sign up to set email alerts
|

LHPP Inhibits the Proliferation and Metastasis of Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) is one of the ten most common cancers in the globe. Despite the diagnosis and treatment of renal cell carcinoma that have made great improvements, the morbidity and mortality rates of renal cell carcinoma remain unchanged remarkably. LHPP is a kind of histidine phosphatases, acting as a tumor suppressor in the progression of various cancers. In this study, we found that LHPP was significantly downregulated in RCC tissues and cell lines. Decreased expression of LHPP was closely correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The results in Figure j and Table S6 show that the Arg biosynthesis pathways (Figure S22a), Arg and proline metabolism pathways (Figure S22b), His metabolism pathways (Figure S22c), and vitamin B6 metabolism pathways (Figure S22d) are mapped, suggesting the relation of these pathways to RCC. These are consistent with the previous reports. …”
Section: Resultssupporting
confidence: 94%
“…The results in Figure j and Table S6 show that the Arg biosynthesis pathways (Figure S22a), Arg and proline metabolism pathways (Figure S22b), His metabolism pathways (Figure S22c), and vitamin B6 metabolism pathways (Figure S22d) are mapped, suggesting the relation of these pathways to RCC. These are consistent with the previous reports. …”
Section: Resultssupporting
confidence: 94%
“…Regulators and substrates of His phosphorylation have been previously linked to roles in tumorigenesis (ACLY(Carrer et al, 2019; Shah et al, 2016), LHPP(Hou et al, 2020; Li et al, 2019; Sun et al, 2020; Wang et al, 2021; F. Wu et al, 2020; Zhang et al, 2020; Zheng et al, 2018), PGAM5(Cheng et al, 2018; Ng Kee Kwong et al, 2018)), and metastasis (ACLY(Wen et al, 2019), PHPT1(Xu et al, 2010), PGAM5(Kang et al, 2015), NME1(Kantor et al, 1993; Khan et al, 2019; Lee et al, 2018; Steeg et al, 1988; Suzuki et al, 2004)) and localize to varying subcellular regions, based upon data from this study and previous publications (detailed in Table 1). Analyzing these proteins and pHis signals in mouse pancreatic tumors, we found that pHis signals were decreased as compared to normal pancreatic tissue and non-tumor or stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…LHPP is closely associated with protein homodimerization and inorganic diphosphatase activity [ 5 , 6 , 8 ]. Recently, an increasing number of publications have suggested that LHPP serves as a tumor suppressor in different tumor types, such as hepatocellular carcinoma (HCC) [ 5 , 27 ], intrahepatic cholangiocarcinoma (ICC) [ 11 ], glioblastoma [ 28 ], melanoma [ 29 ], cervical [ 14 ], bladder [ 10 ], thyroid [ 30 ], pancreatic [ 12 ], renal [ 13 ] and colorectal cancers [ 15 , 16 ]. A reduction in LHPP expression is highly correlated with poor prognosis in patients with malignant diseases.…”
Section: Discussionmentioning
confidence: 99%